2019
DOI: 10.1080/13696998.2019.1620246
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and analysis of efficacy of recombinant factor IX products for prophylactic treatment of hemophilia B in comparison with rIX-FP

Abstract: Aims: Prophylaxis with standard-acting recombinant factor IX (rFIX) in hemophilia B patients requires frequent injections. Extended half-life (EHL) products allow for prolonged dosing intervals, and so reduce this treatment burden. Three technologies are employed to extend the half-life of FIX; glycopegylation, Fc-fusion, and albumin fusion. rIX-FP is a novel albumin fusion protein, which allows for a prolonged dosing interval of up to 14 days. A systematic review and indirect statistical comparison was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…EHLs were safe in our cohort of mainly PTPs, with no patient developing a clinically significant inhibitor during the 6‐month study period. The benefits of EHL concentrates in the Australian population are in keeping with clinical trial results and the growing ‘real‐world’ data showing improved bleeding outcomes despite fewer injections 2‐4. The improvement in bleeding outcomes is likely due to a combination of increased adherence, longer time at higher factor levels and achievement of higher trough factor levels 2.…”
Section: Discussionmentioning
confidence: 54%
“…EHLs were safe in our cohort of mainly PTPs, with no patient developing a clinically significant inhibitor during the 6‐month study period. The benefits of EHL concentrates in the Australian population are in keeping with clinical trial results and the growing ‘real‐world’ data showing improved bleeding outcomes despite fewer injections 2‐4. The improvement in bleeding outcomes is likely due to a combination of increased adherence, longer time at higher factor levels and achievement of higher trough factor levels 2.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, while direct comparisons between products cannot be made, it has been observed that the prophylactic efficacy of rIX-FP is favorable over other standard half-life rFIX and extended half-life products [25]. A systematic literature review indirectly compared the efficacy of rFIX products in adult patients and showed that ABR with 7-day rIX-FP prophylaxis was significantly lower than with standard half-life (p ≤ 0.05) and other extended half-life (p < 0.001) rFIX products (Figure 3) [25]. [8]; rFIXFc, 45 IU/kg (7-day dosing) [26]; rFIX, 100 IU/kg (7-day dosing) [27]; BAX 326, 50.5 IU/kg (2×/weekly dosing) [28]; IB1001, 53 IU/kg (2×/weekly dosing) [29].…”
Section: Clinical Study Data Summarymentioning
confidence: 99%
“…An indirect comparison with N9-GP was neither possible, since mean ABR, AsBR, and AjBR were not provided in the pivotal study [27]; however, rIX-FP achieved a lower median ABR than N9-GP, on 7-day regimen (0.00 vs 1.04). rIX-FP also achieved lower mean ABR values than the SHL-FIX products encompassed in the systematic review [9,28,29].…”
Section: Comparison To Other Ehl-fixmentioning
confidence: 84%
“…A systematic review conducted by Davis and collaborators compared, through indirect statistical comparison, the efficacy of rIX-FP to that of other SHL-FIX and EHL-FIX for prophylaxis treatment of adult patients [9]. On a 7-day regimen, the mean ABR was significantly lower with 35-50 IU/kg of rIX-FP than with 50 IU/kg of rFIX-Fc (1.2 [1.8] vs 3.1 [2.9], p < 0.001).…”
Section: Comparison To Other Ehl-fixmentioning
confidence: 99%
See 1 more Smart Citation